Robust nonsmooth optimality conditions for uncertain multiobjective programs involving stable functions - Van Su, Tran (Positivity : an international journal devoted to the theory and applications of positivity in analysis, 2024)
In this paper, we study and develop robust nonsmooth optimality conditions and duality analysis for an uncertain multiobjective programming problem with constraints (( UCMOP ), for brevity). First, we introduce the constraint qualification of the ( GRSCQ ) type and then establish some robust necessary optimality conditions in terms of the generalized subdifferentials for some types of minima (including robust weakly efficient and robust properly efficient) to such problem involving stable functions. Under suitable assumptions on the pseudo-convexity of objective and constraint functions, robust necessary nonsmooth optimality conditions become robust sufficient optimality conditions. An application of the obtained results for its Wolfe and Mond–Weir types dual problem is presented and some illustrative examples are also provided for our findings.